2006
DOI: 10.1182/blood-2006-02-003087
|View full text |Cite
|
Sign up to set email alerts
|

The transcription factors Scl and Lmo2 act together during development of the hemangioblast in zebrafish

Abstract: The transcription factors Scl and Lmo2 are crucial for development of all blood. An important early requirement for Scl in endothelial development has also been revealed recently in zebrafish embryos, supporting previous findings in scl ؊/؊ embryoid bodies. Scl depletion culminates most notably in failure of dorsal aorta formation, potentially revealing a role in the formation of hemogenic endothelium. We now present evidence that the requirements for Lmo2 in zebrafish embryos are essentially the same as for S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
127
1
3

Year Published

2008
2008
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 138 publications
(136 citation statements)
references
References 47 publications
5
127
1
3
Order By: Relevance
“…LMO2, an SCLbinding partner, is required for erythroid development and is dispensable for the formation of mesoderm and endothelial cells using gene-targeting in mouse embryos and EBs (Warren et al, 1994). These observations from loss-of-function analyses in mouse embryos are supported by those observed in scl and lmo2 morphant embryos using antisense morpholino knockdown in zebrafish Patterson et al, 2005Patterson et al, , 2007Qian et al, 2007). Mis-expression of either scl, or scl and lmo2 Fig.…”
Section: Molecular Pathways Involved In Hemangioblast Developmentmentioning
confidence: 60%
See 2 more Smart Citations
“…LMO2, an SCLbinding partner, is required for erythroid development and is dispensable for the formation of mesoderm and endothelial cells using gene-targeting in mouse embryos and EBs (Warren et al, 1994). These observations from loss-of-function analyses in mouse embryos are supported by those observed in scl and lmo2 morphant embryos using antisense morpholino knockdown in zebrafish Patterson et al, 2005Patterson et al, , 2007Qian et al, 2007). Mis-expression of either scl, or scl and lmo2 Fig.…”
Section: Molecular Pathways Involved In Hemangioblast Developmentmentioning
confidence: 60%
“…This represents the first single gene mutation that eliminates both endothelial and hematopoietic lineages, probably in the level of hemangioblasts. Epistasis analyses have shown that cloche acts upstream of zbp-89, scl, lmo2, gata1, gata2, runx1, c-myb, fli1, flk1, tie2, hhex, and etsrp in hematopoietic and endothelial cell development in zebrafish (Stainier et al, 1995;Fouquet et al, 1997;Liao et al, 1997Liao et al, , 1998Liao et al, , 2000Brown et al, 2000;Burns et al, 2002;Patterson et al, 2005Patterson et al, , 2007Li et al, 2006;Pham et al, 2006;Sumanas and Lin, 2006). In addition, microarray analyses by comparing cloche mutant and wild-type embryos have revealed that cloche specifically regulates a panel of hematopoietic and endothelial genes (Qian et al, 2005;Sumanas et al, 2005;Weber et al, 2005).…”
Section: Molecular Pathways Involved In Hemangioblast Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Overexpression of lmo2 and scl, another key regulator in hemangioblasts, can convert non-axial mesoderm into hemangioblasts (Gering et al, 2003). Consistently, knockdown of lmo2 results in the reduced or lack of expression of genes normally expressed in hematopoietic and vascular endothelial cells (Patterson et al, 2007). Recently, a 2.5-kb genomic regulatory sequence upstream of the translational start site of lmo2 gene was cloned and shown to be able to drive the enhanced green fluorescent protein (EGFP) reporter gene expression specifically in the developing hematopoietic progenitor cells and vascular endothelial cells, which mirrors the endogenous lmo2 expression pattern (Zhu et al, 2005).…”
Section: Introductionmentioning
confidence: 71%
“…scl and lmo2 are expressed in hematopoietic progenitors and endothelial cells, possibly acting together to specify the hemangioblast (Patterson et al 2007). scl encodes a basic helix-loop-helix transcription factor, whereas lmo2 is a LIM-domain transcription factor.…”
Section: Transcriptional Regulators Of Hsc Formationmentioning
confidence: 99%